Putative sugarcane FT/TFL1 genes delay flowering time and alter reproductive architecture in Arabidopsis - Coelho, Carla P.; Minow, Mark A. A.; Chalfun-Júnior, Antonio; Colasanti, Joseph (Frontiers in Plant Science, 2014)
Agriculturally important grasses such as rice, maize and sugarcane are evolutionarily distant from Arabidopsis, yet some components of the floral induction process are highly conserved. Flowering in sugarcane is an important factor that negatively affects cane yield and reduces sugar/ethanol production from this important perennial bioenergy crop. Comparative studies have facilitated the identification and characterization of putative orthologs of key flowering time genes in sugarcane, a complex polyploid plant whose genome has yet to be sequenced completely. Using this approach we identified phosphatidylethanolamine-binding protein (PEBP) gene family members in sugarcane that are similar to the archetypical FT and TFL1 genes of Arabidopsis that play an essential role in controlling the transition from vegetative to reproductive growth. Expression analysis of ScTFL1, which falls into the TFL1-clade of floral repressors, showed transcripts in developing leaves surrounding the shoot apex but not at the apex itself. ScFT1 was detected in immature leaves and apical regions of vegetatively growing plants and, after the floral transition, expression also occurred in mature leaves. Ectopic over-expression of ScTFL1 in Arabidopsis caused delayed flowering in Arabidopsis, as might be expected for a gene related to TFL1. In addition, lines with the latest flowering phenotype exhibited aerial rosette formation. Unexpectedly, over-expression of ScFT1, which has greatest similarity to the florigen-encoding FT, also caused a delay in flowering. This preliminary analysis of divergent sugarcane FT and TFL1 gene family members from Saccharum spp. suggests that their expression patterns and roles in the floral transition has diverged from the predicted role of similar PEBP family members.